Gastroenteropancreatic—origin neuroendocrine carcinomas: Three case reports with favorable responses following localized radiotherapy and a review of literature. Issue 49 (December 2017) - Won, Yong Gyun; Seo, Kyung-Jin; Hyeon, Jiyeon; Shin, Ok Ran; Chang, Eundeok; Sun, Der Sheng; Won, Hae Sung; Ko, Yoon Ho; Na, Sae Jung; Lee, Su Lim; Ku, Young Mi; Lee, Dong Soo
Abstract: Rationale: The radiotherapy (RT) responses of gastroenteropancreatic (GEP)-origin neuroendocrine tumors remain unclear. We report cases of favorable response after localized RT of GEP-origin neuroendocrine carcinomas (GEP-NECs). Patient concerns: 1. An 82-year-old male presented with a lower esophageal mass. Positron emission tomography computed tomography (PET-CT) scan showed a lower esophageal mass and gastrohepatic lymph nodes. 2. A 52-year-old female presented with abdominal discomfort. CT scan showed a 9.8 cm-sized enhancing mass in the lesser sac abutting the stomach, pancreas and liver. 3. A 54-year-old male patient presented with anal pain and bleeding. CT scan showed a remnant mass in the perirectal area after trans-anal excision. Diagnoses: The diagnoses of GEP-NECs were pathologically confirmed by biopsy or excision, and immunohistochemical stainings of Ki-67, CD56, synaptophysin and chromogranin-A. Interventions: 1. The patient was treated with definitive RT. 2. The patient was treated with RT after two cycles of etoposide-cisplatin chemotherapy. 3. The patient was treated with adjuvant RT. Outcomes: 1. Complete remission was achieved based on CT scan four months after RT. 2. CT scan showed partial regression of the mass with a 5 cm-diameter at six months after RT. Adjuvant chemotherapy was administered after RT. 3. The residual mass was almost completely regressed at CT scan four months after RT. Lessons: In cases of GEP-NECs, RT can be a useful treatment modality with favorable tumor response for patients with inoperable conditions or those suffering from bulky tumor masses.